Salivary Biomarkers: A New Wave in Early Disease Detection and Diagnosis (Medical Forum Monthly, 2024)
Salivary biomarkers have emerged as a revolutionary tool in the field of medical diagnostics, offering a non-invasive, accessible, and cost-effective approach for early disease detection and monitoring. This review provides a comprehensive examination of salivary biomarkers, highlighting their diverse roles in diagnosing various health conditions. It delves into the composition of saliva and its diagnostic potential, underscoring the advantages of using saliva over other biological fluids and addressing the challenges associated with saliva collection and analysis. Significant advancements in technology that enhance the detection and analysis of salivary biomarkers are discussed, along with breakthroughs in identifying specific biomarkers for diseases such as cancer, cardiovascular diseases, diabetes, autoimmune disorders, and infectious diseases. Ethical and privacy considerations, particularly concerning consent and the implications of early disease detection, are critically examined.